Pengaruh Bantuan Dana PKH Terhadap Kesejahteraan Masyarakat Miskin (Studi Kasus : Desa Ladang Tuha Kecamatan Pasie Raja Kabupaten Aceh Selatan) - Abubakar, Jariah; Firzan, Khairil (Jurnal Ekonomi Regional Unimal, 2024)
This study aimed to determine the influence of  PKH donation for the welfare of the poverty (case study : Desa Ladang Tuha, Kecamatan Pasie Raja, Kabupaten Aceh Selatan). The data used in this study are primary data obtained from surveys. The data analysis method used in this study is the Multiple Linear Regression Model. The variables studied are free from the classical assumption tests. The results simultaneously show that the income, education, and health goods positively and significantly influenced the poverty in Desa Ladang Tuha, Kecamatan Pasie Raja, Kabupaten Aceh Selatan. This study obtained the value of the coefficient of determination (R2) of 0,624351 or 62,4351 percent, which had a significant effect on the on the poverty in Desa Ladang Tuha, Kecamatan Pasie Raja, Kabupaten Aceh Selatan.